Pemanfaatan Air Limbah Pupuk ZA II Sebagai Penetral pH Dalam IPAL Pabrik Pupuk X - Latifiara Zahra Auly; Euis Nurul Hidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The use of water in industrial activities is a problem that needs to be given strong attention to always be used as a benchmark for water quality, especially in the industrial activities of PT Petrokimia Gresik. This research aims to determine the effectiveness of ZA II factory wastewater as a substitute for NaOH in the pH neutralization process. The effectiveness of ZA II fertilizer wastewater as a pH neutralizer can be determined by testing the pH, TSS and PO4 levels. The method used in this research is neutralization. The variation used is a mixture of neutralized water, NaOH and ZA II waste water. The NaOH used was 0.1 ml; 0.3 ml; 0.5 ml. Based on the research results, it is stated that ZA II fertilizer wastewater can increase pH levels because of its alkaline nature, from 6 to 8. Utilizing ZA II wastewater can reduce the cost of using NaOH, which is relatively expensive. This research can reduce the cost of using NaOH 89.3% cheaper than before, namely IDR 9,000,000/month.